Kajian Literatur: Adopsi Artificial Intelligence (AI) dalam Bidang Jurnalistik - Apriliyanti, Rizki; Atika Sari, Ade Nur; Noor, Riska Aulia (Ideas Publishing, 2024)
The journalism has adopted technology at the next level, where Artificial Intelligence (AI) collaborates in the journalistic field. The aim of this research is to explore AI in the field of journalism and its perceived impact on journalistic products. Literature studies were carried out in international journals indexed by Scopus for 2015-2023. As a result, AI-based journalism is defined as an independent system for collecting, analyzing and processing data through programs created by humans both textually and visually; AI ethics in the form of collecting credible and trustworthy data that has been selected by the editorial team; advantages in the form of being able to overcome contemporary journalistic problems and challenges in the form of journalistic competence.